Development of Islamic Akidah Education in Facing the Era of Society 5.0 - Muhammad Nur Effendi; Suriagiri; Mudhiah (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This study explores the development of Islamic creed education in the era of Society 5.0, focusing on technology integration and the challenges faced. The method used is qualitative, with a case study analysis of several Islamic educational institutions and interviews with educators and parents. Data were collected through observation, in-depth interviews, and literature studies to understand the application of technology in creed education and its impact on the teaching and learning process. The results show that technology integration in Islamic creed education provides significant benefits in increasing the accessibility of teaching materials, enriching teaching methods, and facilitating better interaction between teachers and students. Technologies such as mobile applications, e-learning platforms, and visual aids have expanded the way teaching materials are delivered and made it easier for students to understand the concepts of the creed. However, significant challenges arise from resistance to change, concerns about negative impacts on Islamic values, and the need for educators to be trained to utilize technology effectively. This research emphasizes the importance of a careful and planned approach to integrating technology so that Akidah education remains relevant and aligned with religious principles while accommodating technological developments.